Franz Rosenzweig's and Paul Celan's Early German Translations of Yehudah Halevi's Hebrew Poems - Dal Bo, Federico (Naharaim, 2024)
My paper examines Franz Rosenzweig's and Paul Celan's translations of Yehudah Halevi's poems, approaching the topic from the perspectives of both translation studies and literary criticism. On the one hand, I will scrutinize Rosenzweig's and Celan's translations against the backdrop of their theological approaches. I will also attempt to articulate the translation technique that Celan typically employed throughout his life, while translating from multiple languages into German. On the other hand, I will explore Celan's implicit departure from Rosenzweig and his choice to specifically translate these two poems in light of his poetics, his notion of exile, and his exclusive choice of using German as his only poetic language.